Binding of canonical Wnt ligands to their receptor complexes occurs in ordered plasma membrane environments. (6th July 2017) - Sezgin, Erdinc; Azbazdar, Yagmur; Ng, Xue W.; Teh, Cathleen; Simons, Kai; Weidinger, Gilbert; Wohland, Thorsten; Eggeling, Christian; Ozhan, Gunes
Abstract : While the cytosolic events of Wnt/β‐catenin signaling (canonical Wnt signaling) pathway have been widely studied, only little is known about the molecular mechanisms involved in Wnt binding to its receptors at the plasma membrane. Here, we reveal the influence of the immediate plasma membrane environment on the canonical Wnt–receptor interaction. While the receptors are distributed both in ordered and disordered environments, Wnt binding to its receptors selectively occurs in more ordered membrane environments which appear to cointernalize with the Wnt‐receptor complex. Moreover, Wnt/β‐catenin signaling is significantly reduced when the membrane order is disturbed by specific inhibitors of certain lipids that prefer to localize at the ordered environments. Similarly, a reduction in Wnt signaling activity is observed in Niemann–Pick Type C disease cells where trafficking of ordered membrane lipid components to the plasma membrane is genetically impaired. We thus conclude that ordered plasma membrane environments are essential for binding of canonical Wnts to their receptor complexes and downstream signaling activity. Abstract : Heterogeneous plasma membrane organization is crucial for its function. Here, using biochemical and biophysical tools, we show that canonical Wnt binding to its receptor complex occurs preferentially in ordered membrane environments, which are enriched with saturated lipids and cholesterol. These ordered membrane regions are cointernalized with the canonical Wnt‐receptor complex and initiate the β‐catenin‐dependent Wnt signaling.